The african tale the owner of fire and water and aesthetic dimensions: studies, reflections and experiences on a literacy class (Research, Society and Development, 2019)
This article aims to present the african tale the power of fire and water, a literary work of the author Celso Sisto (2012) and illustrations of  Reuben Son, as an element from the African culture. The bibliographic survey was based on aesthetic dimensions that analyzes the illustrative elements and the narrative text, under the ethnic-cultural aspect of the African Continent, using the reading strategies advocated by Ceslo Sisto (2012), Hannah Arguelho Aparecida de Souza (2010) and Jose Auri Cunha (2005). The research participant was developed with an interactive activity of mediation of reading in a literacy class in the municipality of Volta Redonda. We underline the importance of the dialogical interaction between the participants in the cultural relevance, predominantly rooted in the origin of brazilian civilization, such as the tradition of popular tales and the preservation of folk memory by the counters of history, passed down from generation the other, in addition to the beauties and riches of mysticism by means of illustrative images, which by means of imaging and textual narrative, has the purpose of expressing during the dialogical practice, reflective thinking of aesthetic dimensions of african tale to understand the historical context and ethnic-cultural african and afro-brazilian, recognizing it as a producer of culture.